Microsporogénesis de tres especies del subgénero Passiflora (Passiflora, Passifloraceae) de Paraguay - Pereira Suhsner, Claudia Diana (2016)
The aim of the present study was to characterize karyologically species of Passiflora L. from Félix Pérez Cardozo District, Guairá, Paraguay. The chromosome numbers in meiosis 2n = 9II for P. alata Curtis and P. caerulea L. are reported for the first time. Chromosome number for P. edulis Sims (2n = 9II) is also confirmed. Meiotic behaviour in all studied species was normal with regular chromosome segregation. The most frequent chromosome associations were bivalents at diakinesis and metaphase I. Few meiotic irregularities were observed, such as lagging chromosomes and asynchronous phases of meiosis II, however, pollen viability was high, between 78.83% and 98.6%. The obtained results confirms x = 9 as the basic chromosome number for subgenus Passiflora. The present study is a rele¬vant contribution to the knowledge on the cytogenetics of species of Passiflora subg Passiflora from Paraguay.